A Time for Metabolism and Hormones - Sassone-Corsi, Paolo; Christen, Yves.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Recent years have seen spectacular advances in the field of circadian biology. These have attracted the interest of researchers in many fields, including endocrinology, neurosciences, cancer, and behavior. By integrating a circadian view within the fields of endocrinology and metabolism, researchers will be able to reveal many, yet-unsuspected aspects of how organisms cope with changes in the environment and subsequent control of homeostasis. This field is opening new avenues in our understanding of metabolism and endocrinology. A panel of the most distinguished investigators in the field gathered together to discuss the present state and the future of the field. The editors trust that this volume will be of use to those colleagues who will be picking up the challenge to unravel how the circadian clock can be targeted for the future development of specific pharmacological strategies toward a number of pathologies.
The Epigenetic And Metabolic Language Of the Circadian Clock -- Molecular Architecture of the Circadian Clock in Mammals -- Circadian Mechanisms in Bioenergetics and Cell Metabolism -- Control of metabolism by central and peripheral clocks in Drosophila -- Circadian post-transcriptional control of metabolism -- Redox and Metabolic Oscillations in the Clockwork -- Rev-erbs: Integrating Metabolism Around the Clock -- Control of sleep-wake cycles in Drosophila -- Circadian metabolomics: insights for biology and medicine -- Rhythms within rhythms: the importance of oscillations for glucocorticoid hormones -- The genetics of autism spectrum disorders. .
Keywords: Human physiology; Endocrinology; Cytology; Neurosciences; Human Physiology; Endocrinology; Cell Biology; Neuroscience